Staphylococcus aureus methicillin-resistant in healthcare professionals - Bullé, Danielly Joani (2016)
Aim: To determine the prevalence of asymptomatic carriers of Staphylococcus aureus resistant to methicillin (MRSA) in the nasal mucosa of health professionals. Method: Cross-sectional study with 29 health professionals from a teaching hospital, from March to April 2012, through the collection swab of the the nasal mucosa. Microbiological tests were performed at the University of Santa Cruz do Sul. The data were analyzed descriptively and it was given an α risk <5% (p<0.05) and 95% confidence interval. Results: S. aureus was isolated in nasal mucosa of 26 of the 29 (89.6%) health professionals, and 7 (26.9%) were MRSA. The profession most affected by MRSA were nursing technicians, nurses and students with less time of work in the institution. Conclusion: The observed prevalence of colonization of health professionals by S. aureus and MRSA was high, constituting a risk for patients